Perspectives on Federal transportation Policy - Miller, James Clifford; American Enterprise Institute for Public Policy Research (Washington: American Enterprise Institute for Public Policy Research, 1975)
This paper is based on the proceedings of a two-day conference organized by the American Enterprise Institute for Public Policy Research in Washington, D.C. The presentations made at the conference were categorized into six sections. The first two sections analyze Government regulation of surface and air transportation; the third deals with different approaches to problem solving among economists and Government officials, the fourth analyzes four Federal transportation programs, and the fifth and sixth present the responses of transportation policy makers to the questions raised.
Proceedings of a conference held in Washington, D.C., Feb. 1974, sponsored by American Enterprise Institute for Public Policy Research.
Includes bibliographical references.
ne 21/02/2018
Loan
Keywords: Transportation and State